Sources of financing the activities promoting sport and physical education on the basis of the example of Polish foundations and associations - Mamcarczyk Mariola; Zieniuk Paweł (Management, 2020)
At present 177 thousand associations and 26 thousand foundations operate in Poland, which are involved in many different areas of public benefit activities and finance their activities from various sources. The paper presents the results of own studies carried out on a sample of 100 public benefit organisations conducting activity in the area of supporting and promoting physical education and sport. The main objective of the paper concerns presentation of the possibilities of acquiring funds by the organisations to carry out the statutory tasks associated with the development of sport and physical education and the structure of sources of financing this activity in practice of Polish foundations and associations. The paper analyses legal regulations and domestic and subject literature, presenting possible financing sources of activity of Polish organisations. The empirical studies were carried out based on analysis of the content of substantive reports of public benefit organisations. The verification of statistical hypotheses was carried out using the structure indicator test. The results of the conducted studies confirm the main hypothesis, according to which the public benefit organisations finance the activity promoting sport and physical education mainly from public sources, with the funds originating from the local government budgets playing the most important role. The paper also presents the results regarding the structure of the funds originating from private sources and the mechanism of 1% of personal income tax. The paper tackles the subject seldom discussed in the literature and can play a role in the discussion on the system of financing the public benefit activities given the dynamic development of non-government organisations sector.